Identification of Qualitative Characteristic Bali Polled Cattle - Zulkharnaim Maupa; Sudirman Baco; Lellah Rahim; Muhammad Yusuf (Hasanuddin Journal of Animal Science (HAJAS), 2021)
The aim of the research was to identify the qualitative characteristics of Bali polled cattle.  Several advantages in polled cattle can reduce the risk of injury that often occurs in herdsmen’s caused by horns, can prevent bruising of the carcass and damage to the skin. The development of Bali polled cattle requires further research, this research is related to its qualitative characteristics. The total sample was 100 consisting of 11 Bali polled cattle and 89 Bali horned cattle, consisting of 42 samples from Bone Regency and 47 samples from Barru Regency.  Qualitative characteristics that are measured include: coat color, blackline runs along the back, color of socks, color of rump, muzzle color, eyelid color, white hair in the ears, and wattle size.  The qualitative characterization of Bali Cattle in this study was based on the Indonesian Institute of Sciences (LIPI) ́s guidelines for phenotypic characterization. The distinctive characteristics found in horned Bali cattle are also found in polled cattle. The presence of Bali polled cattle changes the indigenous cattle rearing system in Indonesia.